The contribution of paid vacation time to wellbeing among employed Canadians. Issue 1 (2nd January 2016) - Hilbrecht, Margo; Smale, Bryan
ABSTRACT: Vacations provide an opportunity to relax, recover from the demands of work, and spend time with family and friends. Recently, however, concerns have been expressed regarding the low uptake of paid vacation time among Canadian workers and its potential impact on their quality of life. Guided by the conservation of resources theory, we examined the extent to which Canadian employees use their paid vacation allotment and how the amount of paid vacation time is related to feelings of wellbeing. A subsample of 3, 451 people who worked full-time at a paid job or business was drawn from Statistics Canada's 2010 General Social Survey. More than one-third of Canadian employees reported taking less than the minimum amount of federally mandated paid vacation time (10 days) during the previous year. This included 19.3% who reported taking no paid vacation days at all. Factors significantly associated with uptake of vacation days were age, socio-economic status, having younger children in the household, flexible work schedules and occupational sector. Fewer than half of agriculture, accommodation and food services, and construction sector employees took the minimum amount of paid vacation days. Linear regression analysis with mediation indicated that taking more paid vacation days was positively associated with both overall health and life satisfaction. The relationship for each factor was partially mediated by feelings of time pressure, satisfaction with work–life balance, and self-assessed mental health. Findings suggest the need to examine sector-specific workplace cultures and management practices in order to encourage employees to take their full vacation allotment.